Multiple HPV genotype infections in cervical cancer progression in the Study to Understand Cervical Cancer Early Endpoints and Determinants (SUCCEED) - Wentzensen, Nicolas (2009)
Determining the causal attribution of HPV genotypes to cervical disease is important to estimate the effect of HPV vaccination and to establish a type spectrum for HPV-based screening. We analyzed the prevalence of HPV infections and their attribution to cervical disease in a population of 1670 women referred to colposcopy for abnormal cytology at the University of Oklahoma. HPV genotyping was performed from cytology specimens using the Linear Array assay that detects 37 HPV genotypes. We used different methods of type attribution to revised cervical disease categories. We found very high prevalence of multiple HPV infections with up to 14 genotypes detected in single specimens. In all disease categories except for cancers, there was a significant trend of having more infections at a younger age. We did not see type interactions in multiple genotype infections. HPV16 was the most frequent genotype at all disease categories. Based on different attribution strategies, the attribution of vaccine genotypes (6, 11, 16, 18) ranged from 50.5% to 67.3% in cancers (n=107), from 25.6% to 74.8% in CIN3 (n=305), from 15.2% to 52.2% in CIN2 (n=427), and from 6.6% to 26.0% in <CIN2 (n=708). In the HSIL cytology group (n=651), attribution ranged from 26.1% to 64.7%. The attribution of vaccine types to HSIL was substantially higher compared to the lower cytology categories. The potential range of HPV genotype attribution is wide at the disease categories <CIN2 to CIN3. Genotyping from cervical lesions and analyzing viral oncogene expression can improve estimates of HPV genotype attribution.